2013
DOI: 10.1002/jssc.201300310
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of nine anticoagulant rodenticides in soil and water by LCESIMS

Abstract: A new and sensitive analytical method is presented to determine nine anticoagulant rodenticide (chlorophacinone, bromadiolone, pindone, diphacinone, warfarin, coumatetralyl, brodifacoum, floucomafen, and difenacoum) residues in water and soil samples by LC-ESI-MS. Rodenticides were extracted from soil using a methanol and ammonium formate 30 mM mixture, while ethyl acetate was employed in the water samples. A Gemini 5 μm C18 column was employed, and a mobile phase comprising a mixture of ammonium formate 30 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…As mentioned above, there are very few studies that determine ARs in soil and none of them analyze difethialone residues. Moreover, the LOQ and LOD values obtained with our modified QuEChERS method are much lower than those obtained using other extraction methodologies [27,29,31] except for brodifacoum, coumatetralyl, difenacoum and flocoumafen, whose LOQs are in the same range than those obtained with a MeOH and ammonium format extraction [28]. However, it should be noted that the LOD and LOQ in those cases were established as three and ten times the S/N of the blank sample extract, respectively, while ours were calculated following the more restrictive criteria of the European Union SANTE guidance [58].…”
Section: In House Validation Studiescontrasting
confidence: 53%
See 1 more Smart Citation
“…As mentioned above, there are very few studies that determine ARs in soil and none of them analyze difethialone residues. Moreover, the LOQ and LOD values obtained with our modified QuEChERS method are much lower than those obtained using other extraction methodologies [27,29,31] except for brodifacoum, coumatetralyl, difenacoum and flocoumafen, whose LOQs are in the same range than those obtained with a MeOH and ammonium format extraction [28]. However, it should be noted that the LOD and LOQ in those cases were established as three and ten times the S/N of the blank sample extract, respectively, while ours were calculated following the more restrictive criteria of the European Union SANTE guidance [58].…”
Section: In House Validation Studiescontrasting
confidence: 53%
“…Along with a robust extraction method, adequate detection analysis is necessary. ARs and PhACs have been determined mainly by liquid chromatography (LC) with different detectors such as UV [32,51], diode array (DAD) [30,52], DAD with fluorescence detectors (FLD) [53,54] and single quadruple mass spectrometry (MS) detectors [28,55]. However, the preferred option when looking for sensitivity and selectivity at trace level is liquid chromatography-tandem mass spectrometry (LC-MS/MS) [7,35,56,57], which is the best option for low-level residues that can be expected to be found in soils.…”
Section: Introductionmentioning
confidence: 99%
“…It is the case when baits are directly available without protection or when they are washed away and diluted in sea or river. In Spain, a study on water and soil samples revealed no imminent environmental risk in treated areas with chlorophacinone and brodifacoum [79]. However, the use of secured bait stations prevents this kind of exposition.…”
Section: Wildlife Exposures and Intoxicationmentioning
confidence: 99%
“…As past research has shown, the loss of a major predator or predators could severely impact the balance of a sensitive or well-established ecosystem (Sergio et al, 2008 andZielinski, 2014). In addition to these effects in the trophic cascade, ARs may also persist in our ecosystem posing more environmental concerns (Hernández et al, 2013, Liu et al, 2015.…”
Section: Discussionmentioning
confidence: 99%